Hyperbaric oxygen therapy prevents subarachnoid hemorrhage-induced apoptosis and impaired contractility of the rabbit bladder - ŞEKERCİ, ÇAĞRI AKIN; ŞENER, GÖKSEL; TARCAN, TUFAN (WILEY, 2020)
Aim To explore the effects of experimental subarachnoid hemorrhage (SAH) on rabbit urinary bladder and to assess the potential protective effects of hyperbaric oxygen therapy (HBOT). Methods A total of 15 male New Zealand white rabbits were divided randomly to one of three groups: group I was spared as the control group (n = 5), group II was exposed to SAH, received no treatment, and acted as the SAH group (n = 5) and group III was exposed to SAH and received five sessions of HBOT (started 12 hours after SAH induction and was given twice daily for the first 2 days and once on the third day) and acted as the treatment group (n = 5). At 72 hours after the SAH induction, bladders from all animals were removed for in vitro organ bath experiments and biochemical analyses. Results Isometric tension studies revealed that compared to group I, the contractile responses of the strips to carbachol in group II were significantly decreased whereas HBOT restored the contractile responses (P < .05). Caspase-3 and nitric oxide synthase (NOS) activities of bladder tissues were significantly increased in group II when compared with group I, whereas caspase-3 and NOS activities were significantly decreased in the tissues of group III (P < .01). Conclusions Subarachnoid hemorrhage stimulates apoptosis of the rabbit bladder and impairs the contractile response of the rabbit bladder to carbachol. HBOT creates a protective effect in rabbit bladder tissues and restores SAH-induced changes.
Keywords: apoptosis; hyperbaric oxygene therapy; subarachnoid heamorrhage; urinary bladder; CEREBRAL-ISCHEMIA; DYSFUNCTION; DAMAGE; TIME